2009
DOI: 10.1007/s10531-009-9754-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effectiveness of enforcement strategies for avoiding tropical deforestation in Kerinci Seblat National Park, Sumatra

Abstract: As the tropical deforestation crisis continues, innovative schemes are being developed to reduce this loss, such as the sale of forest carbon credit. Nevertheless, to address this ongoing and pervasive loss, governments, protected area managers and donors need to know where to invest their limited conservation resources for greatest success. At the moment this prioritisation is rarely done objectively, so there is a need for new methods that predict the efficacy of different approaches. In this study, we focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
2
16
0
1
Order By: Relevance
“…The spatial patterns of deforestation across this area highlighted the critical role of accessibility, with the importance of distance to roads and residential areas. These results reflect the findings of other deforestation assessments (Ludek et al 1990;Linkie et al 2004Linkie et al , 2010Amini et al 2009;Bagheri, Shataee 2010). It was found that 83% of deforestation occurred within a 2-km distance from roads.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The spatial patterns of deforestation across this area highlighted the critical role of accessibility, with the importance of distance to roads and residential areas. These results reflect the findings of other deforestation assessments (Ludek et al 1990;Linkie et al 2004Linkie et al , 2010Amini et al 2009;Bagheri, Shataee 2010). It was found that 83% of deforestation occurred within a 2-km distance from roads.…”
Section: Discussionsupporting
confidence: 89%
“…The logistic regression goodness of fit is low, suggesting that missing variables such as livestock's role, might further explain differences between low and high deforestation. In spite of this, the modelling approach developed by this study would benefit conservation planning (Wilson et al 2005;Smith et al 2008;Linkie et al 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Linkie et al (2010) showed that focused long-term patrols can be effective in deterring illegal activities in and around Sumatran protected areas. In Peninsular Malaysia, enforcement efforts by DWNP thus far have been commendable (Table 3) (Table 3).…”
Section: Anti-poaching Patrolsmentioning
confidence: 99%
“…Deforestation rates are higher in areas inhabited by people, highlighting the need for alternate livelihoods, active forest protection and community involvement in conservation (Galvin et al 2006;Linkie et al 2010). Furthermore, other anthropogenic threats, including hunting, illegal wildlife trade and human-wildlife conflict demonstrate that the inclusion of communities in conservation strategies is integral to success.…”
Section: Community-based Conservationmentioning
confidence: 99%